E-PRINT SYSTEM IN UNIMAS - Nur Alia, Mohd Yusof (Universiti Malaysia Sarawak (UNIMAS), 2019)
As a university student, printing documents has become an important part of the entire academic life, whether it is for learning materials, reports, assignments, or thesis. However, the current problems faced by university students are they get through the hassle and time-consuming at printing services provided in Universiti Malaysia Sarawak (UNIMAS). Therefore, the E-Print System is proposed as a solution for this problem. This project aims to develop a web-based printing service for students in UNIMAS. This web-based printing service is designed for users to print out their documents and provide them with beneficial printing service without consuming much time. This project consists ofsix chapters; introduction, literature review, requirement analysis, and design, implementation, testing, conclusion, and future work. The chosen methodology to develop the E-Print System in UNIMAS is Waterfall Model. Limitations of existing systems are identified to come out with better solutions. Some background study is carried out to investigate how the current technology is used for printing document. Besides, the system is designed according to the result of requirement analysis. Several software tools are installed and configured in the development of the E-Print System, such as XAMPP and phpMyAdmin. Last but not least, the expected outcome of this project is to establish a functional web-based system for printing service in UNIMAS.